Single site design considerations in onfarm experiments - Walker, P. (1991)
I do not propose to say much about the type of verification trial where a single plot using a package of improvements is established on the fields of several farmers. Although they often provide useful information over an area, I consider them to be little more than demonstration plots. Where we have several plots per site, on the other hand, we are forced towards experiments